A Content Analysis of Displayed Alcohol References on a Social Networking Web Site - Moreno, Megan A (2010)
PURPOSE: Exposure to alcohol use in media is associated with adolescent alcohol use. Adolescents frequently display alcohol references on Internet media such as social networking websites (SNSs). The purpose of this study was to conduct a theoretically-based content analysis of older adolescents’ displayed alcohol references on a SNS. METHODS: We evaluated 400 randomly selected public MySpace profiles of self-reported 17 to 20-year-olds from zip codes representing urban, suburban and rural communities in one Washington county. Content was evaluated for alcohol references suggesting: 1) explicit versus figurative alcohol use, 2) alcohol-related motivations, associations and consequences, including references that met CRAFFT problem drinking criteria. We compared profiles from four target zip codes for prevalence and frequency of alcohol display. RESULTS: Of 400 profiles, 225 profiles (56.3%) contained 341 references to alcohol. Profile owners who displayed alcohol references were mostly male (54.2%) and White (70.7%). The most frequent reference category was explicit use (49.3%), the most commonly displayed alcohol use motivation was peer pressure (4.7%). Few references met CRAFFT problem drinking criteria (3.2%). There were no differences in prevalence or frequency of alcohol display among the four sociodemographic communities. CONCLUSIONS: Despite alcohol use being illegal and potentially stigmatizing in this population, explicit alcohol use is frequently referenced on adolescents’ MySpace profiles across several sociodemographic communities. Motivations, associations and consequences regarding alcohol use referenced on MySpace appear consistent with previous studies of adolescent alcohol use. These references may be a potent source of influence on adolescents, particularly given that they are created and displayed by peers.